2018
DOI: 10.1007/s00296-018-4016-2
|View full text |Cite
|
Sign up to set email alerts
|

Physician–patient communication in rheumatology: a systematic review

Abstract: The nature of physician–patient interaction can have a significant impact on patient outcomes through information-sharing and disease-specific education that can enhance patients’ active involvement in their care. The aim of this systematic review was to examine all the empirical evidence pertaining to aspects of physician–patient communication and its impact on patient outcomes. A systematic search of five electronic databases (MEDLINE, PsycINFO, EMBASE, CINAHL, and Web of Science) was undertaken from earlies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 41 publications
4
57
0
Order By: Relevance
“…The analysis revealed an imbalance between trust and mistrust in the rare disease field, whereby a trusting patient-physician relationship is a prerequisite for effective communication. Georgopoulou, Prothero, and D’Cruz [35], Dowell et al [13], and the Royal Pharmaceutical Society of Great Britain, Merck, Sharp, and Dohme [14] all link a trusting relationship with a physician to many positive healthcare outcomes. Von der Lippe, Diesen, and Feragen [36] further deepen this analysis by describing a mistrust of doctors, and linking this to patients’ emotional reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed an imbalance between trust and mistrust in the rare disease field, whereby a trusting patient-physician relationship is a prerequisite for effective communication. Georgopoulou, Prothero, and D’Cruz [35], Dowell et al [13], and the Royal Pharmaceutical Society of Great Britain, Merck, Sharp, and Dohme [14] all link a trusting relationship with a physician to many positive healthcare outcomes. Von der Lippe, Diesen, and Feragen [36] further deepen this analysis by describing a mistrust of doctors, and linking this to patients’ emotional reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the concept has been successfully employed across different disciplines including medical science, psychotherapy, and learning environments (i.e., schools and university). In these fields, evidence for the positive effects of good patientphysician, patient-therapist, and student-teacher working alliance on clinical, psychological treatment, and learning outcomes are accumulating (e.g., Derksen, Bensing, & Lagro-Janssen, 2013;Fuertes, Toporovsky, Reyes, & Osborne, 2017;Georgopoulou, Prothero, & D'Cruz, 2018;Horvath, Del Re, Fluckiger, & Symonds, 2011;Rogers, 2015;van Osch, van Dulmen, van Vliet, & Bensing, 2017). Thus, the status quo should inspire researchers to systematically approach the issue of rapport building in witness interviews in different age groups, testing the isolated and combined effects of different rapport building components (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Georgopoulou et al . [ 13 ] carried out a recent systematic review and concluded that more research was required to increase understanding of the patient–physician relationship in rheumatology. The physician–patient relationship is vital, because it has an impact on patient outcomes and satisfaction with treatment and care [ 13 ] and on various behaviours, although only medication adherence has been studied in any depth [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%